Effect of Therapeutic Hypothermia and Mesenchymal Stromal Cells on Ultrastructure of Ratsâ€™ Cardiomyocytes with Experimental Myocardial Infarction - Trofimova, Ðnna V.; Chyzh, Nikolay A.; Repin, Nikolay V.; Belochkina, Irina V.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):166.